1983
DOI: 10.1037/0096-1523.9.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Information integration and the identification of stimulus noise and criterial noise in absolute judgment.

Abstract: Two main classes of theories have been proposed regarding range effects in unidimensional absolute-identification tasks. One class posits that as range is increased, .criterial noise increases but stimulus noise remains constant. Another class posits increasing stimulus noise but constant criterial noise. In this study, an effort is made to help decide this issue. Multiple observations are used in several absolute-identification tasks of varying range. A stimulus integration model is proposed in which averagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 22 publications
4
85
1
Order By: Relevance
“…Predictions of this averaging rule have been confirmed in several experiments by explicitly manipulating the number of stimulus presentations given to the subject or the time preceding a decision (see, e.g., Nosofsky, 1983;Swets & (1) (2) CTt = 2CT~+CTE Bonnel et al (1987) from a more general framework suggested by Luce and Green (1978). First, we will describe the basic Thurstonian model for the same-different task as it has been used in focused attention experiments (e.g., Dickman & Meyer, 1988;Egeth & Blecker, 1971;Moss, Myers, & Filmore, 1970).…”
Section: The Sample-size Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…Predictions of this averaging rule have been confirmed in several experiments by explicitly manipulating the number of stimulus presentations given to the subject or the time preceding a decision (see, e.g., Nosofsky, 1983;Swets & (1) (2) CTt = 2CT~+CTE Bonnel et al (1987) from a more general framework suggested by Luce and Green (1978). First, we will describe the basic Thurstonian model for the same-different task as it has been used in focused attention experiments (e.g., Dickman & Meyer, 1988;Egeth & Blecker, 1971;Moss, Myers, & Filmore, 1970).…”
Section: The Sample-size Modelmentioning
confidence: 83%
“…Values of ul were estimated for each condition, by using that both (1: and (1~would be influenced by changes in (11 comes from Nosofsky (1983), who developed a modelbased technique for estimating sensory and criterion variance in identification tasks. He applied this technique in several conditions differing in the physical range over which stimuli varied, and he found evidence that both sensory and criterion variance increased with stimulus range.…”
Section: Lomentioning
confidence: 99%
“…Recall that during the perceptual matching task, the stimulus exposure duration was unlimited, whereas during identification, the stimulus exposure duration was 100 msec. Thus, the observer could obtain more perceptual information on each trial during the matching task, resulting in less perceptual variability (Green & Swets, 1967;Luce, 1986;Nosofsky, 1983). In addition, the decision problem is different in the two tasks, which will likely lead to differences in criterial noise.…”
Section: Predicting Identification From Perceptual Matchingmentioning
confidence: 99%
“…Separate estimates of perceptual and criterial noise have been obtained in the past (see, e.g., Nosofsky, 1983), but these have required a comparison of performance across several different experiments.…”
Section: Decision Bound Theorymentioning
confidence: 99%